Use of the superficial circumflex iliac artery perforator flap for reconstruction after sarcoma resection. Issue 4 (11th January 2021) - Yoshimatsu, Hidehiko; Karakawa, Ryo; Fuse, Yuma; Tanakura, Kenta; Yamamoto, Takumi; Okada, Akira; Daniel, Bassem W.; Yano, Tomoyuki
Abstract: Background: Postoperative complications after flap‐coverage in sarcoma treatment can postpone postoperative adjunct treatments. Here, we present our experience with the use of the superficial circumflex iliac artery perforator (SCIP) flap after sarcoma resection. Patients and Methods: Patients undergoing immediate reconstruction surgery with a flap after sarcoma resection at a single institution from February 2017 to April 2020 were identified. Patient demographics, tumor characteristics, surgical characteristics, and complications were examined. Results: Thirty‐five consecutive patients underwent reconstructions using a SCIP flap (34 free and one pedicled SCIP flaps). We also identified 47 consecutive patients who underwent reconstruction with other pedicled or free flaps over the same time period. No significant differences were found in patient age, gender, defect size, or operative time between these two groups. The incidences of overall complications (20/47 [42.6%] vs. 3/35 [8.5%], p < .001), flap dehiscence (7/47 [14.8%] vs. 0/35 [0%], p = .018), and total flap complications (15/47 [31.9%] vs. 2/35 [5.7%], p = .005) were statistically greater in the control group than in the SCIP group. Conclusion: With its minimal postoperative complication rate both in the reconstruction site and the donor site, the SCIP flap can be considered an optimal reconstruction option after sarcoma resection.